Rising From Adversity: Unveiling Filipino Muslims’ Motivation and Interest In Pursuing Career Success Through Education - Ontok-Balah, Khadiguia (International Research-Based Education Journal, 2023)
This case study explores the triumphant path of four resilient Maguindanawn individuals who braved the obstacles by quitting school but eventually returned to meet their academic goals. Focusing on their motivation to persist, the study explores how these individuals recognized the pivotal role of higher education in achieving professional success. Through in-depth interviews, the participants shared their unique experiences of dropping out and returning to school, shedding light on the challenges and triumphs they faced along the way. Careful selection criteria ensured that the study included Maguindanawn individuals with the drive to complete a degree and emerge as an accomplished professional. This study underscores the critical role of determination and resilience in surmounting obstacles and achieving career success. This compelling study investigates the myriad reason behind school dropouts among Maguindanawn students, from financial hardships to armed conflicts in their communities. One participant even suffered from psychiatric illness due to the trauma of armed conflicts. However, these obstacles did not thwart the determination of the participants to pursue their academic goals with tenacity. Through their perseverance, they excelled professionally, gained invaluable leadership skills, and served as shining examples for future Maguindanawn students. This study highlights the crucial role of education in achieving professional success and fulfilling personal aspirations. It emphasizes the need for schools in Moro-dominated areas to promote education as a vehicle for financial stability, fulfilling religious duties, and succeeding in the workplace, inspiring all students, particularly dropouts, to return to the classroom.